Biomechanical Characterization of a New Acellular Dermal Matrix for Oral Soft Tissue Regeneration. Issue 6 (1st June 2022) - Pabst, Andreas; Sagheb, Keyvan; Blatt, Sebastian; Sagheb, Kawe; Schröger, Saskia; Wentaschek, Stefan; Schumann, Sven
Abstract: Objectives: Acellular dermal matrices (ADM) are a suitable alternative to autogenous soft tissue grafts (ASG). The aim of this study was to analyze the biomechanical properties and architectural features of ASG and ADM. Materials and methods: ASG were harvested from the hard palate of fresh frozen body donors as connective tissue grafts and compared to ADM of porcine origin (NovoMatrix, NM; mucoderm, MD). Maximum load (ML, Newton [N]) and expansion (E, [mm]) were measured after rehydration in saline solution by tensile strength measurement. Light microscopy (LM) and scanning electron microscopy (SEM) were performed to analyze the architectural features of ASG and ADM in high resolution. Results: ASG demonstrated a significantly decreased ML compared to NM and MD ( p < 0.0001 and p = 0.019). NM showed a significantly increased ML compared to MD ( p = 0.001). ASG demonstrated a non-significantly reduced E compared to NM ( p = 0.13) and a significantly increased E compared to MD ( p = 0.025). NM showed an increased E compared to MD ( p < 0.0001). LM and SEM highlighted the surface characteristics and internal structures of ASG and ADM, such as the surface compact layer of MD and the densely packed, parallel running and ordered collagen fibers of NM and MD. Conclusions: Significant differences concerning the biomechanical properties and architectural features of ASG, and ADM were found. Clinical relevance: Information about the biomechanical properties and architectural features of ASG and ADM can contribute to a better understanding of the clinical performance and extend the application area.